Magnitude and factors associated with benign prostatic hyperplasia among adult male patients visiting Wolaita Sodo University comprehensive specialized hospital southern Ethiopia - Tirufat Tiruneh; Tamiru Getachew; Firdawek Getahun; Tesfaye Gebreyesus; Simeon Meskele (Scientific Reports)
Abstract Worldwide, in Africa and Ethiopia prevalence of Benign Prostatic Hyperplasia among patients with lower urinary tract symptoms was 26.2%, 44.2%, and 33.4% respectively. However, there is limited evidence regarding Benign Prostatic Hyperplasia in southern Ethiopia and it was not well explored. Therefore, this study aimed to assess the magnitude and associated factors of Benign Prostatic Hyperplasia among adult male patients visiting Wolaita Sodo University Comprehensive Specialized Hospital, southern Ethiopia 2022. A hospital-based cross-sectional study was conducted from July to September 2022. A systematic random sample technique was employed to select 376 participants. Data were gathered using a structured questionnaire and entered, cleaned, coded, and analyzed using SPSS Version 25.0. To describe the study respondents, descriptive statistics were used. Bivariate and multivariate analyses were conducted and an adjusted odd ratio with 95% Confidence Interval (CI) was utilized to quantify the degree of association, and statistical significance was declared at p-value < 0.05. A total of 376 male patients admitted to the surgical department of the Urology ward were included in this study and the magnitude of Prostatic Hyperplasia was 21.3%; 95% CI: 17.3, 25.8. The vegetable consumption, fruit consumption, physical activity, sleeping time and sexual dysfunction [(AOR = 7.57, 95% CI: (2.78, 20.60)], [(AOR = 21.06,95% CI: (7.06,27.53)], [(AOR = 0.57,95% CI: (0.19, 0.67)], [(AOR = 3.23, 95% CI: (1.18,8.79)] and [(AOR = 17.05, 95% CI: (4.82,60.28)] were factors associated with Benign Prostatic Hyperplasia respectively. The benign prostatic hyperplasia is a prevalent disease among men in this study. Sexual dysfunction, consumption of vegetables, consumption of fruits, practice of physical activity and sleeping time were factors associated with BPH. Hence, screening programs for higher-risk people to ensure the early presentation of benign prostatic hyperplasia and practicing eating balanced diets are vital areas to reduce the prevalence.